Hydrolytic depolymerization of corncob lignin in the view of a bio-based rigid polyurethane foam synthesis. Issue 10 (18th January 2017) - Xue, Bai-Liang; Huang, Pan-Li; Sun, Yong-Chang; Li, Xin-Ping; Sun, Run-Cang
Abstract : Corncob lignin was efficiently depolymerized in an isopropanol–water mixture with NaOH as catalyst into bio-polyols with low molecular weight and suitable hydroxyl number in view of the preparation of a bio-based rigid polyurethane foam. Abstract : Corncob lignin was efficiently depolymerized in an isopropanol–water mixture with NaOH as catalyst into bio-polyols with low molecular weight and suitable hydroxyl number in view of the preparation of a bio-based rigid polyurethane foam. The effects of process parameters including the reaction temperature, NaOH concentration, isopropanol–water ratio and reaction time on the product yields were investigated. The depolymerized lignin (DL) products obtained were further analyzed by GPC, FT-IR, 2D-HSQC NMR, 31 P-NMR, GC-MS and thermogravimetric analysis. The results showed that 22.1% DL with a low molecular weight (860 g mol −1 ) and a suitable hydroxyl number (5.10 mmol g −1 ) together with 5.1% solid residue was obtained under an optimum condition (at 280 °C, 5% NaOH in 25% isopropanol–water ratio for 15 min). In short, this depolymerization process would effectively produce the bio-polyols, which would have great potential as a polyol substitution for partial incorporation into rigid polyurethane foams.